Pengaruh Likuiditas, Profitabilitas, Leverage dan Biaya Operasional Terhadap Agresivitas Pajak Pada Sektor Transportasi dan Logistik Yang Terdaftar Di BEI Periode 2011 -2021 - Dinda Aulia; Agustina Suparyati (Student Scientific Creativity Journal, 2023)
This research was conducted to analyze the effect of Liquidity, Profitability, Leverage and Operating Costs on Tax Aggressiveness in Transportation and Logistics sector companies listed on the Indonesia Stock Exchange for the period 2011 – 2021. The sampling technique used was purposive sampling so that the number of samples used in the study were 15 companies. The data analysis method in this study uses panel data regression analysis techniques. The results of this study indicate that Liquidity, Profitability and Leverage have a negative effect on Tax Aggressiveness. Meanwhile, operational costs have a positive influence on tax aggressiveness